TPM Technopark Sdn Bhd / Mohamad Haziq Mohd Zam Zam - Mohd Zam Zam, Mohamad Haziq (2017)
In this industrial report, there were consisted of four chapters. For chapter 1 consists of background company, organizational structural, products, and market strength. Then, chapter 2 consists of exposure level while chapter 3 consists of nature of work, problem encountered and how to overcome it and experienced gained. Chapter 4 consists of lessons learned, knowledge gained, suitability of organization and limitations and recommendations. TPM Technopark Sdn Bhd was chosen as place for internship. This company was involving more than two project in Johor Bahru but there are an options was giving by company to choose for placement site throughout two months of training.